Interleukin-1β and interferon-γ are associated with malaria-induced hypoinsulinemic hypoglycemia in Plasmodium berghei ANKA-infected mice - Rujikorn Rattanatham,; Voravuth Somsak, (Penerbit Universiti Kebangsaan Malaysia, 2022)
Malaria-induced hypoglycemia is recognized as a serious complication of malaria and has one of the strongest associations with mortality in children. It has been speculated that oxidative stress and pro-inflammatory response during parasite infection were involved in its pathophysiology. Hence, this study aimed to investigate the development of malaria-induced hypoglycemia during Plasmodium berghei ANKA (PbANKA) infection with particular attention to the involvement of c-peptide, interleukin-1β (IL-1β), and interferon-γ (IFN-γ). ICR mice were infected with 1×107 parasitized erythrocytes of PbANKA, and parasitemia was monitored, and the development of hypoglycemia was assessed by measuring plasma glucose levels. The change of c-peptide level was evaluated. The pro-inflammatory response of IL-1β and IFN-γ were also quantified in plasma. It was found that PbANKA infection resulted in hypoglycemia as indicated by a significantly (P < 0.05) decrease in plasma glucose levels on day 4 post-infection and associated with parasitemia. The c-peptide was slightly increased at day 2 post-infection, and then significantly (P < 0.05) decreased since day 4. Furthermore, we observed a significantly (P < 0.05) increased IL-1β, firstly responded, at day 2 post-infection followed by increasing the IFN-γ level at day 4 in PbANKA-induced hypoglycemia. Our findings support the idea that hypoinsulinemic hypoglycemia in the PbANKA infected mice may be involved in the high IL-1β and IFN-γ against the parasite infection.